Natural product, bilobalide, improves joint health in rabbits with osteoarthritis by anti-matrix degradation and antioxidant activities - Ma, Tianwen; Chen, Hong; Ruan, Hongri; Lv, Liangyu; Yu, Yue; Jia, Lina; Zhao, Jinghua; Li, Xin; Zang, Yuxin; Xu, Xinyu; Zhang, Jiantao; Gao, Li (Frontiers in Veterinary Science, 2022)
Osteoarthritis (OA) is a common chronic musculoskeletal disease reported in veterinary clinics that severely reduces the quality of life of animals. The natural product, bilobalide, has positive effects on chondroprotection but its exact mechanism of action is unclear. This study aimed to investigate the antioxidant and anti-matrix degradation activities of bilobalide in a rabbit model of OA and its protective effects on joints. We also investigated the possible mechanisms underlying these effects. The rabbit OA model was established by intra-articular injection of 4% papain. Thirty healthy male New Zealand rabbits were randomly divided into control, untreated OA, Cel (100 mg/kg celecoxib intervention as a positive control), BB-L and BB-H (40 mg /kg and 80 mg /kg bilobalide gavage treatment, respectively) groups. Two weeks after surgical induction, bilobalide or celecoxib was administered by gavage daily for eight weeks. After eight weeks of bilobalide intervention, cartilage macroscopic observation and histopathological images showed alleviation of cartilage damage after bilobalide treatment, and the Osteoarthritis Research Society International (OARSI) score was significantly lower than that in the OA group. Bilobalide reduced the expression of metalloproteinase 3 (MMP3) and MMP13 in cartilage tissue of OA rabbits and reversed the levels of serum C-telopeptides of type II collagen (CTX-II), cartilage oligomeric matrix protein (COMP), interleukin 1(IL-1), and tumor necrosis factor (TNF-α). Bilobalide (80 mg/kg) could improve the biomechanical properties and microstructural changes in subchondral bone in the early stage of OA in rabbits, thereby delaying subchondral bone damage. Mechanistically, bilobalide exerted antioxidant and anti-matrix degradation effects by upregulating the oxidative stress signaling Nrf2/HO-1 pathway and inhibiting cartilage degeneration in rabbit OA. We thus speculate that bilobalide supplements recovery from OA damage.